[μ-1,2-Bis(diphenylphosphino)methane-κ(2) P:P′]bis{[(Z)-O-ethyl N-(4-nitrophenyl)thiocarbamato-κS]gold(I)} - Ho, Soo Yei (International Union of Crystallography, 2010)
Each gold atom in the binuclear title compound, [Au(2)(C(9)H(9)N(2)O(3)S)(2)(C(25)H(22)P(2))], is coordinated within an S,P-donor set that defines a slightly distorted linear geometry [S—Au—P angles = 172.77 (6) and 173.84 (6)°], with the distortion due in part to a close intramolecular Au⋯O contact [2.968 (11) and 2.963 (4) Å]. The molecule adopts a U-shaped conformation allowing for the formation of an aurophilic Au⋯Au interaction [3.2320 (5) Å]. Molecules are consolidated in the crystal structure by C—H⋯π interactions. Disorder was noted for one of the ethoxy groups with two orientations being resolved in a 0.679 (16):0.321 (16) ratio.